Thiophene-derived polymer dots for imaging endocytic compartments in live cells and broad-spectrum bacterial killing - Prasad, Kenath Priyanka (2017)
In this work, we present a new type of polymer dot synthesized from bithiophene (pTh-Pdot) via a simple and high yield procedure. Owing to their high brightness, excellent photo-stability, good biocompatibility, and molecular size, pTh-Pdots are promising for bioimaging applications. As a proof-of-concept demonstration, pTh-Pdots are herein employed to track the endocytic pathway in live cells. Furthermore, we show that these polymeric nanoparticles can serve as potent antibacterial agents by making use of their ability to disrupt bacterial membranes and high peroxidase mimicking activity.